IMPLEMENTATION OF THE BRAINSTORMING METHOD IN THE STUDY OF BIOLOGICAL CHEMISTRY IN A MEDICAL HIGHER EDUCATION INSTITUTION - Григор’єва, Надія; Велика, Алла; Кропельницька, Юлія (SWorldJournal, 2026)
The article describes the experience of the faculty at Bukovinian State Medical University in teaching biological chemistry to future medical and pharmaceutical specialists. The authors propose methodologies for implementing interactive teaching methods,